2017
DOI: 10.1016/j.ijsu.2017.10.075
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic distal pancreatectomy: A comparative study of clinical outcomes and costs analysis

Abstract: RDP showed lower conversion rate and shorter hospital stay than LDP at the price of longer operative time. RDP is financially comparable to LDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Fifth, the time from the diagnosis to the treatment was an important element that may affect the outcome of therapy, which however was not included into our study due to the lack of data in the original literature. Sixth, complications should be classified into different severity levels by Clavien-Dindo scoring system [37, 38], which unfortunately cannot be performed due to the lack of relevant data in the original literature.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the time from the diagnosis to the treatment was an important element that may affect the outcome of therapy, which however was not included into our study due to the lack of data in the original literature. Sixth, complications should be classified into different severity levels by Clavien-Dindo scoring system [37, 38], which unfortunately cannot be performed due to the lack of relevant data in the original literature.…”
Section: Discussionmentioning
confidence: 99%
“…17 In comparison, a study from Spain demonstrated no significant difference (RDP: 9198.64 € vs LDP: 9399.74 €; p > 0.5) between the two approaches. 18 Waters et al reported that the cost of RDP was lower ($ 10,588) compared with the laparoscopic ($ 12,986) procedure because of a shorter length of stay. 19 Kang et al found RDP to be 2.5 times more expensive than LDP ($ 8304 vs. $ 3861).…”
Section: Discussionmentioning
confidence: 99%
“…12 Ielpo et al also demonstrated the same offsetting of high start-up costs associated with RDP as reduced LOS, as well as reduced use of surgical staplers and energy devices compared with LDP. 13 However, other studies suggest RDP is considerably more costly than LDP, owing to start-up and maintenance costs -although there is wide variation in cost calculation methodology and assumptions. 9 Kang et al provide a Korean perspective, reporting a 2.5-fold increase in costs with RDP compared with LDP.…”
Section: Pancreas Surgerymentioning
confidence: 99%
“…In addition to material costs and LOS, operating time is also a contributor to the overall cost. Most studies report a significantly longer operating time for RDP compared with LDP, 8,[12][13][14][16][17][18] which may in part be due to the 30 minutes required to dock and undock the robot, and in part due to the learning curve effect in RDP. In the largest series by Zureikat et al including 83 RDP, longer operating times are reported early in the series but eventually become equivalent to both the LDP and OPD series by the end of the 4-year experience.…”
Section: Pancreas Surgerymentioning
confidence: 99%